C 0 C 1 + 2 C 1 C 2 + 3 C 2 C 3 + … + 1 5 C 1 4 C 1 5
Let C r denote the binomial coefficient ( r 1 5 ) . What is the value of the expression above?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Simpler last line:
n = 0 ∑ 1 4 ( n + 1 ) n + 1 1 5 − n = n = 0 ∑ 1 4 ( 1 5 − n ) = 1 5 + 1 4 + 1 3 + … + 2 + 1 = …
Note that f(k) = (k+1) * 15C(k+1)/15Ck = (k+1)(k!)(15-k)! / (k+1)!(14-k)! = 15-k. So the required sum is 15+14+...+1 = 15(15+1)/2 = 120.
C(r)/C(r-1) = (n+1)/r - 1 And T(r) = r * C(r)/C(r-1) = (n+1) - r Thus Sum = n(n+1) - n(n+1)/2 = n(n+1)/2 Putting n = 15, you get 120
Since × is between 1 and 15, inclusive, l simplified the fraction ( x 1 5 ) / ( ( x − 1 ) 1 5 ) which came out to ( 1 6 − x ) / x . Thus, the problem can be rewritten as ∑ i = 1 1 5 x ( ( 1 6 − x ) / x ) = ∑ i = 1 1 5 ( 1 6 − x ) = ( 1 5 × 1 6 ) / 2 = 1 5 × 8 = 1 2 0
C x − 1 C x = ( x − 1 ) ! ( 1 5 − x + 1 ) ! 1 5 ! x ! ( 1 5 − x ) ! 1 5 ! = x 1 6 − x
C 0 C 1 + 2 C 1 C 2 + 3 C 2 C 3 + … + 1 5 C 1 4 C 1 5 = x = 1 ∑ 1 5 x C x − 1 C x = x = 1 ∑ 1 5 x x 1 6 − x = x = 1 ∑ 1 5 1 6 − x = x = 1 ∑ 1 5 1 6 − x = 1 ∑ 1 5 x = 1 5 × 1 6 − 2 1 5 × 1 6 = 2 1 5 × 1 6 = 1 2 0
Problem Loading...
Note Loading...
Set Loading...
Note first that for 0 ≤ n ≤ 1 4 we have that
C n C n + 1 = ( 1 5 − n ) ! ∗ n ! 1 5 ! ( 1 4 − n ) ! ∗ ( n + 1 ) ! 1 5 ! = n + 1 1 5 − n .
So the desired sum is
n = 0 ∑ 1 4 ( n + 1 ) n + 1 ( 1 5 − n ) = 1 5 ∗ n = 0 ∑ 1 4 ( 1 ) − n = 0 ∑ 1 4 n = 1 5 ∗ 1 5 − 2 1 4 ∗ 1 5 = 1 2 0 .